PERLINDUNGAN HAK BAGI PELAKU USAHA MASKAPAI PENERBANGAN SESUAI DENGAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI KASUS PUTUSAN PENGADILAN NEGERI NO. 10/PDT.SUS-BPSK/2016/PN.JKT.BRT JO. PUTUSAN BPSK NO. 006/A/BPSK-DKI/XII/2015) - Viola Monica; Ahmad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2021)
The Airline has the obligation to compensate for losses suffered due to damage or loss of consumer goods. However, based on the applicable laws and regulations, not all damage or loss of items in the aircraft baggage is borne by the airline service provider. This study aims to describe the responsibilities that must be borne by airlines based on Law No.8 of 1999 concerning consumer protection and Law No.1 of 2009 concerning aviation and also to see the protection of the rights of airlines in the BPSK Decision No. 006 / A / BPSK-DKI / XII / 2015. This study uses the normative method and uses a library study of aviation-related statutory documents and interviews with related parties. The result of this research is that compensation is given if checked baggage, namely the baggage given to the airline at check-in is lost or damaged, while for cabin baggage where the goods carried by the consumer are not covered by the company. From the BPSK's decision in the Leo Christoffel case, Qatar Airways as an airline has suffered a lot because it is asked to bear half of the losses suffered by consumers. This is clearly not in accordance with the flight law where lost in cabin baggage will not be compensated by the airline.